Digestibility and metabolic utilisation of diets containing chestnut tannins and their effects on growth and slaughter traits of heavy pigs. Issue 1 (2nd January 2019) - Galassi, Gianluca; Mason, Federico; Rapetti, Luca; Crovetto, Gianni M.; Spanghero, Mauro
Abstract: This research aims at evaluating the effects of the dietary addition of a supplement containing 75% of chestnut tannins (CT) on growth performance, slaughter traits (Experiment 1) and on nutrient utilisation (Experiment 2) of Italian heavy pigs. Exp. 1 compared a control (C) diet with diets containing 0.15 or 0.30% of CT supplement. Forty-two barrows (91 ± 6 kg of BW) were divided into pairs and kept in 21 partially-slatted pens equipped with individual feeding (7 pens/diet). Animals were slaughtered at a BW of 174 ± 6 kg. The CT inclusion did not modify the performance and the slaughter traits but lowered the intensity of red colour ( p  < .05) and brightness (p  < .05) of the gastric mucosa. Exp. 2 measured digestibility of nutrients, nitrogen (N) balance and energy utilisation of a C diet compared with low protein diets containing 0 or 0.53% of CT supplement (low protein, LP and low protein plus tannins, LPT, respectively). Eighteen barrows (BW 153 ± 4 kg) were housed in 6 metabolic cages in 3 periods of 14 days, with 6 animals per diet. LPT pigs produced less urine than LP (2132 vs. 2561 g/d, p <  .05) and both were lower than C (2978 g/d, p <  .05). LP and LPT diets had similar digestibility (87.6 vs. 87.8% for DM, and 85.1 vs. 83.9% for CP). N and energy balance were similar among all diets (34.8, 39.0, 39.2% retained N, and 37.6, 35.7, 37.3% retained energy, for C, LP and LPT, respectively). In conclusion, tannins do not exert anti-nutritional effect at the concentrations applied. Highlights: Dietary chestnut tannin (CT) addition (at 1.5–5.3 g/kg) does not modify digestibility, metabolic use of nutrients and performance of heavy pigs. Dietary CT addition reduces urine volumes of animals with potential impact on farm slurry management. Changes of colour and hypertrophy of gastric mucosa of pigs fed CT are proxy indicators of metabolic reactions to be further investigated.